2021
DOI: 10.7554/elife.65557
|View full text |Cite
|
Sign up to set email alerts
|

Dimerisation of the PICTS complex via LC8/Cut-up drives co-transcriptional transposon silencing in Drosophila

Abstract: In animal gonads, the PIWI-interacting RNA (piRNA) pathway guards genome integrity in part through the co-transcriptional gene silencing of transposon insertions. In Drosophila ovaries, piRNA-loaded Piwi detects nascent transposon transcripts and instructs heterochromatin formation through the Panoramix-induced co-transcriptional silencing (PICTS) complex, containing Panoramix, Nxf2 and Nxt1. Here, we report that the highly conserved dynein light chain LC8/Cut-up (Ctp) is an essential component of the PICTS co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 85 publications
3
25
0
Order By: Relevance
“…(b) Hypothetical model showing the condensation of multiple Piwi–piRNA silencing complexes. Possible formation of LLPS is suggested in recent studies (Eastwood et al., 2021; Schnabl et al., 2021)…”
Section: The Pirna‐guided Silencing Pathway In Drosophila Regulates Te‐inserted Genomic Regionsmentioning
confidence: 82%
See 2 more Smart Citations
“…(b) Hypothetical model showing the condensation of multiple Piwi–piRNA silencing complexes. Possible formation of LLPS is suggested in recent studies (Eastwood et al., 2021; Schnabl et al., 2021)…”
Section: The Pirna‐guided Silencing Pathway In Drosophila Regulates Te‐inserted Genomic Regionsmentioning
confidence: 82%
“…Nxf2 associates with the nascent transcript of target TEs to form a silencing complex. Recent studies have suggested that Panx can further associate with Cut‐up/LC8 and form a dimerized structure, suggesting the possibility that the Piwi–piRNA silencing complex can form a liquid‐liquid phase separation (LLPS) (Eastwood et al., 2021; Schnabl et al., 2021) (Figure 4b). HP1a, which is recruited to H3K9me, and the linker histone H1 are further associated with the piRNA target regions to induce a stable heterochromatin structure (Huang et al., 2013; Iwasaki et al., 2016; Le Thomas et al., 2013; Rozhkov et al., 2013).…”
Section: The Pirna‐guided Silencing Pathway In Drosophila Regulates Te‐inserted Genomic Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Piwi in embryos showed high levels of antisense piRNAs targeting roo (~16% or all TE-targeting reads) and 297 (~9%), consistent with an ability of maternally deposited Piwi to potentially recognize these TEs when expressed in the embryo. In Drosophila ovaries, coTGS depends on Piwi-mediated recruitment of the PICTS/SFiNX complex and correlates with the deposition of H3K9me3 marks at TE insertions and surrounding genomic regions (Batki et al, 2019;Eastwood et al, 2021;Fabry et al, 2019;Murano et al, 2019;Schnabl et al, 2021;Sienski et al, 2015;Yu et al, 2015;Zhao et al, 2019). Due to the poor conservation of the genomic locations of transposon insertions between different Drosophila strains, we used whole genome sequencing to de novo identify the TE insertion sites present in our control w 1118 flies (see methods).…”
Section: -Figure Supplement 1n O)mentioning
confidence: 99%
“…Recently, Panoramix (Panx), a protein that functions in the piRNA pathway was also shown to dimerize in a Dlc-dependent manner (Eastwood et al, 2021;Schnabl et al, 2021). Artificial dimerization of a panx mutant that could no longer interact with Dlc (using the same GCN4 leucine zipper) restored the function of panx (Eastwood et al, 2021;Schnabl et al, 2021).…”
Section: The Role Of Egl Dimerizationmentioning
confidence: 99%